Improved efficacy with targeted pharmacogenetic-guided treatment of patients with depression and anxiety: A randomized clinical trial demonstrating clinical utility. (January 2018) - Bradley, Paul; Shiekh, Michael; Mehra, Vishaal; Vrbicky, Keith; Layle, Stacey; Olson, Marilyn C.; Maciel, Alejandra; Cullors, Ali; Garces, Jorge A.; Lukowiak, Andrew A.
Abstract: The objective of this study was to evaluate the effect of pharmacogenetics-guided treatment on patients diagnosed with depression and/or anxiety, in a diverse set of clinical settings, as compared to the standard of care. The trial design followed a prospective, randomized, subject- and rater-blinded approach enrolling 685 patients from clinical providers specializing in Psychiatry, Internal Medicine, Obstetrics & Gynecology, and Family Medicine. The NeuroIDgenetix ® test uses a genetic variant panel of ten genes, along with concomitant medications, to make medication management recommendations based on gene-drug and drug-drug interactions for over 40 medications used in the treatment of depression and anxiety. Pharmacogenetic testing was performed at the initial screening visit and baseline patient assessments were determined using the 17-item Hamilton Rating Scale for Depression (HAM-D17) and the Hamilton Rating Scale for Anxiety (HAM-A). Following enrollment and randomization, pharmacogenetic results for subjects assigned to the experimental group were provided to physicians to guide treatment selection, while control subjects were treated according to the usual standard of care. HAM-D17 and HAM-A assessments were collected at 4 weeks, 8 weeks, and 12 weeks after baseline to assess the efficacy of therapeutic selection. In patients diagnosed with depression, response rates (p = 0.001; OR: 4.72 [1.93–11.52]) and remission rates (p = 0.02; OR: 3.54 [1.27–9.88]) were significantly higher in the pharmacogenetics-guided group as compared to the control group at 12 weeks. In addition, patients in the experimental group diagnosed with anxiety showed a meaningful improvement in HAM-A scores at both 8 and 12 weeks (p = 0.02 and 0.02, respectively), along with higher response rates (p = 0.04; OR: 1.76 [1.03–2.99]). From these results, we conclude that pharmacogenetic-guided medication selection significantly improves outcomes of patients diagnosed with depression or anxiety, in a variety of healthcare settings.